Thermal management solution for PCB using integrated heat pipes - Koh, Cadance Jing Suan (2017)
In almost all industrial electronic applications, the use of PCB is indispensable. Indubitably, it will introduce heat localisation and there has been many research done in the aspect of a finer thermal control management. It is not unfamiliar that a scaled-down cooling system is often in demand for today’s electronic design but this will pose further impediment for the PCB to dissipate heat more efficaciously. The current traditional cooling techniques includes the use of bulky heat sinks and external cooling fins which will only drags down the overall aesthetic appearance of an electronic component and the purpose of miniaturisation. Furthermore, the use of external cooling devices demonstrated that the modern cooling method acts as another separate unit from the PCB. This concern has hence led to the urge of amalgamating cooling devices with the PCB as a single unit. The report sets to put forward an embedded thermal management solution for PCB using flat heat pipes and pyrolytic graphite sheets. With a more demanding market for miniaturised heat pipes and to cater for the increasing performance demands, the prototyping of an efficient thermal control system has become progressively challenging. A two-phase cooling solution approach will be analysed in this report where heat pipes will be introduced for its high thermal coefficients for heat transfer. With the integrative design approach of the heat pipes, new means of dissipating heat from electronic devices will be dully examined. In this project, a flat heat pipe will be integrated with the laminated structure of a PCB during. In retrospect, the goal of this project sets to explore on the feasibility of a more effectual thermal management solution with an integrated heat pipe technology. Additionally, one of the scrutinise is to consider the amount of current the board can withstand and the allowance for heat localisation to happen on the board. The contemporary approach will hence enhance the design flexibility of an electronic product holistically and, to propose a more viable thermal control system through the prediction of thermal characteristics using integrated heat pipes.